Colocalization of cortical microtubules and F-actin in Dipodascus magnusii using confocal laser scanning microscopy - Hasek, J; Trachtulcová, P; Kohlwein, S D; Streiblová, E (Folia microbiologica, 2003)
Distribution of microtubules and F-actin in aerobically growing cells of Dipodascus magnusii, belonging to the class Saccharomycetes was analyzed using immunofluorescence microscopy and labeling with rhodamine-tagged phalloidin. A conspicuous system of permanent cytoplasmic microtubules was observed in association with multiple nuclei. In elongating cells, helices of cytoplasmic microtubules appeared at the cell cortex. In cells approaching cytokinesis transversely oriented microtubules were revealed at incipient division sites. Confocal laser scanning microscopy showed a continuity of these transverse microtubules with the remaining microtubule network. The actin system of D. magnusii consisted of patches and filaments. Patches were found to accumulate at the tips of growing cells. Bands of fine actin filaments were usually observed before F-actin rings were established. A close cortical association of microtubules with the F-actin ring was documented on individual optical sections of labeled cells. Cells with developing septa showed medial F-actin discs associated at both sides with microtubules. Colocalization of cytoplasmic microtubules with actin filaments at the cortex of dividing cells supports a role of both cytoskeletal components in controlling cell wall growth and septum formation in D. magnusii.
Keywords: mikrotubuly; rhodaminy; buněčné dělení; Fluorescent Antibody Technique; Microscopy, Confocal; aktiny; Microtubules; konfokální mikroskopie; Actins; Cell Division; Rhodamines; Phalloidine; Saccharomycetales; fluorescenční protilátková technika; faloidin